KARAKTERISTIK MENTOR PADA KEGIATAN PELATIHAN DASAR CALON PEGAWAI NEGERI SIPIL CPNS - ATPRIATNA UTAMA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The mentoring program in basic training activities for civil servant candidates aims to improve the professionalism of civil servants at the beginning of community service. The relationship between mentors and mentees is fundamental and crucial to realizing the goals of mentors and mentees. This study aims to determine the character of the mentor's